Development of National Cancer Database for Cost and Quality of Life (CaDCQoL) in India: a protocol. Issue 7 (29th July 2021) - Prinja, Shankar; Dixit, Jyoti; Gupta, Nidhi; Mehra, Nikita; Singh, Ashish; Krishnamurthy, Manjunath Nookala; Gupta, Dharna; Rajsekar, Kavitha; Kalaiyarasi, Jayachandran Perumal; Roy, Partha Sarathi; Malik, Prabhat Singh; Mathew, Anisha; et al.
Abstract : Introduction: The rising economic burden of cancer on healthcare system and patients in India has led to the increased demand for evidence in order to inform policy decisions such as drug price regulation, setting reimbursement package rates under publicly financed health insurance schemes and prioritising available resources to maximise value of investments in health. Economic evaluations are an integral component of this important evidence. Lack of existing evidence on healthcare costs and health-related quality of life (HRQOL) makes conducting economic evaluations a very challenging task. Therefore, it is imperative to develop a national database for health expenditure and HRQOL for cancer. Methods and analysis: The present study proposes to develop a National Cancer Database for Cost and Quality of Life (CaDCQoL) in India. The healthcare costs will be estimated using a patient perspective. A cross-sectional study will be conducted to assess the direct out-of-pocket expenditure (OOPE), indirect cost and HRQOL among cancer patients who will be recruited at seven leading cancer centres from six states in India. Mean OOPE and HRQOL scores will be estimated by cancer site, stage of disease and type of treatment. Economic impact of cancer care on household financial risk protection will be assessed by estimating prevalence of catastrophic health expenditures and impoverishment. The national database would serve as a unique open access data repository to derive estimates of cancer-related OOPE and HRQOL. These estimates would be useful in conducting future cost-effectiveness analyses of management strategies for value-based cancer care. Ethics and dissemination: Approval was granted by Institutional Ethics Committee vide letter no. PGI/IEC-03/2020-1565 of Post Graduate Institute of Medical Education and Research, Chandigarh, India. The study results will be published in peer-reviewed journals and presented to the policymakers at national level.